PEMIKIRAN-PEMIKIRAN FONETIK IBNU JINNI (W. 392 H. / 1002 M.) - Arifuddin Arifuddin (Arabic Literature Department, 2013)
This article discusses phonetic thoughts of Ibnu Jinni, scientist who became a central figure in the development of Arabic phonetics. His work named Sirru Shinâ‟atil I‟râbis the first phonetic book in Arabic. He also called this science with terminology„Ilmul-Ashwât which is still used by Arabic scientist until now. These features are behindthe writing of this article. This article to describe Ibnu Jinni curriculum vitae, the bookSirru Shinâ‟atil-I‟râb, and phonetic thoughts of Ibnu Jinni and his contribution in Arabicphonetic progress The conclusion is that Ibnu Jinni has given big contribution in Arabicphonetic progress. The most important thing is his research about vowel. There are somany vowel studied and be the main reference for the next study.